2018
DOI: 10.3389/fphys.2018.01220
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Atrophy Due to Nerve Damage Is Accompanied by Elevated Myofibrillar Protein Synthesis Rates

Abstract: Muscle loss is a severe complication of many medical conditions such as cancer, cardiac failure, muscular dystrophies, and nerve damage. The contribution of myofibrillar protein synthesis (MPS) to the loss of muscle mass after nerve damage is not clear. Using deuterium oxide (D2O) labeling, we demonstrate that MPS is significantly increased in rat m. tibialis anterior (TA) compared to control (3.23 ± 0.72 [damaged] to 2.09 ± 0.26%∗day−1 [control]) after 4 weeks of nerve constriction injury. This is the case de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 51 publications
1
31
1
Order By: Relevance
“…All bands on the membrane (Fig. 3B,C) were normalized to total protein content per corresponding lane on the gel (Supplement S2 and S3) as described previously 12,[16][17][18] .…”
Section: Elevated Levels Of Proteins Associated With Membrane Damagementioning
confidence: 99%
See 4 more Smart Citations
“…All bands on the membrane (Fig. 3B,C) were normalized to total protein content per corresponding lane on the gel (Supplement S2 and S3) as described previously 12,[16][17][18] .…”
Section: Elevated Levels Of Proteins Associated With Membrane Damagementioning
confidence: 99%
“…The secondary antibodies were applied accordingly and the membrane imaged via infrared imaging (Odyssey, LI-COR Biosciences, USA). We and others have previously found that normalizing protein levels to housekeeping proteins is less reliable than normalizing to total protein content 12,16,17 . We therefore normalized all levels of our proteins to total protein content of the gel stained with Coomassie Blue.…”
mentioning
confidence: 92%
See 3 more Smart Citations